Artificial neural networks for diagnosis of hepatitis disease - Ozyilmaz, L; Yildirim, T (IEEE, 2003)
Recently, neural networks have become a very important method in the field of medical diagnostic. The objective of this work is to diagnose hepatitis disease by using different neural network architectures. Standard feedforward networks and a hybrid network were investigated. Results obtained show that especially the hybrid network can be successfully used for diagnosing of hepatitis.
Keywords: Computer Science